Перспективи мобільних технологій. Flutter - Червінська, А. Л. (ХНУРЕ, 2025)
Mobile technologies are fundamentally changing the very nature of communication and professional operations. Due to this architecture, Flutter, the framework behind cross-platform applications introduced by Google became an essential tool in developing mobile, web and desktop apps all using the same code base. Flutter design interface usability, as compared to other technologies such as React Native or Xamarin, provides higher performance and ease of use in interface design. Current trends include integration with Material 3 Design, graphics enhancements through Impeller, and support for artificial intelligence.
Keywords: мобільна технологія; платформа Flutter